Measuring the willingness to pay to avoid guilt: estimation using equilibrium and stated belief models - Charles Bellemare; Alexander Sebald; Martin Strobel (Institute for the Study of Labor (IZA), 2010)
We estimate structural models of guilt aversion to measure the population level of willingness to pay (WTP) to avoid feeling guilt by letting down another player. We compare estimates of WTP under the assumption that higher-order beliefs are in equilibrium (i.e. consistent with the choice distribution) with models estimated using stated beliefs which relax the equilibrium requirement. We estimate WTP in the later case by allowing stated beliefs to be correlated with guilt aversion, thus controlling for a possible source of a consensus effect. All models are estimated using data from an experiment of proposal and response conducted with a large and representative sample of the Dutch population. Our range of estimates suggests that responders are willing to pay between 0.40 and 0.80 Euro to avoid letting down proposers by 1 Euro. Furthermore, we find that WTP estimated using stated beliefs is substantially overestimated (by a factor of two) when correlation between preferences and beliefs is not controlled for. Finally, we find no evidence that WTP is significantly related to the observable socio-economic characteristics of players.
Keywords: C93; D63; D84; 330; Guilt aversion; willingness to pay; equilibrium and stated beliefs models; Soziale Beziehungen; Willingness to pay; Test